Achievable Data Rate in Hybrid MIMO Cognitive Radio Networks. (2016) - Satheesan, U.; Sudha, T.
Abstract: Cognitive radio plays a vital role in wireless communication. Hybrid cognitive radio networks work in both underlay and overlay modes. The data rate of such hybrid cognitive radio network is limited. MIMO system can be implemented in hybrid cognitive radio networks for improving the data rate. Beam forming is used over the MIMO antennas to reduce the interference level in the desired direction. The game model called Nash Equilibrium (NE) is used for power control in secondary users (SUs) and primary users (PUs). Our investigations show that the achievable data rate increases due to the applied beam forming technique in MIMO antennas for hybrid cognitive radio network.